A new species of Mimothrix Majer, 1989 (Coleoptera: Dasytidae) from Xizang, China - Miao, Jia-Lin; Liu, Hao-Yu; Tong, Jun-Bo; Yang, Xing-Ke; Yang, Yu-Xia (Zootaxa, 2026)
A new dasytid species of the genus Mimothrix Majer, 1989 is discovered from Mêdog, Xizang, China, and described as M. medogensis Yang & Miao, sp. nov. The description is supported by illustrations of the habitus, pygidium, abdominal sternite VIII, and genitalia of both sexes. The new species can be readily distinguished from other species of Mimothrix by its relatively short and stout median lobe, which is regularly shaped at base and blunt at apex. Additionally, M. montivaga Majer, 1995, is redescribed in detail and illustrated with habitus, pygidium and abdominal sternite VIII of both sexes, as well as the female genitalia for the first time, to make comparison with the new species.